Mobile Application Informasi Wisata Surakarta Berbasis Android - Rico Renandiansyah; Ernes Cahyo Nugroho (Go Infotech: Jurnal Ilmiah STMIK AUB, 2017)
In this study discusses the existing tourist information in the city of Surakarta (Solo), Solo with a total area of 44.40 KM2. Keraton and Batik, Klewer Market makes three things that make the identification of Surakarta. The execution of the Surakarta Hadiningrat Palace and Pura Mangkunegaran, making Solo a historical, artistic, and cultural axis that has a selling point. The selling value is manifested by ancient buildings and preserved traditions and impressive artwork. No wonder if Solo became one of the tourist destination that is very attractive for tourists to visit in Solo. Lack of existing tourist information that some have not been exposed by many print and electronic media therefore tourists who want to visit the city of Solo will be a little confusion in searching for existing tourist information. The purpose of research to design and build Mobile Application Information Surakarta Tour Based Android, By using waterfall method. System design using java programming language and PHP version 5.6.8, Android Studio version 2.2.3, UML, MySQL database version 5.6.21. The results of solo travel applications are expected to provide solutions for travelers by utilizing the integration of GPS (Global Positioning System), as well as service directions from the Google Map that produces information about the tours that are displayed on solo travel applications or just want to see the existing tourist information.  Keywords : Surakarta Tour, Android Application, Android Studio version 2.2.3,  GPS.